Efficacy, safety and drug survival of conventional agents in pediatric psoriasis: A multicenter, cohort study - SALMAN, ANDAÇ; SEÇKİN GENÇOSMANOĞLU, DİLEK; ERGUN, SAFİYE ATLAS TÜLİN (WILEY, 2017)
The data on long-term efficacy, safety and drug survival rates of conventional systemic therapeutics in pediatric psoriasis is lacking. The primary aim of this study is to investigate acitretin, methotrexate, cyclosporin efficacy, safety and drug survival rates in pediatric patients as well as predictors of drug survival. This is a multicenter study including 289 pediatric cases being treated with acitretin, methotrexate and cyclosporin in four academic referral centers. Efficacy, adverse events, reasons for discontinuation, 1, 2- and 3-year drug survival rates, and determinants of drug survival were analyzed. A 75% reduction of Psoriasis Area and Severity Index score or better response rate was obtained in 47.5%, 34.1% and 40% of the patients who were treated with acitretin, methotrexate and cyclosporin, respectively. One-year drug survival rates for acitretin, methotrexate and cyclosporin were 36.3%, 21.1% and 15.1%, respectively. The most significant determinant of drug survival, which diminished over time, was treatment response whereas arthritis, body mass index and sex had no influence. Although all three medications are effective and relatively safe in children, drug survival rates are low due to safety concerns at this age group. Effective disease control through their rational use can be expected to improve survival rates.
Keywords: drug survival; efficacy; pediatric; psoriasis; systemic treatment; CHILDHOOD PSORIASIS; ETANERCEPT; CHILDREN; METHOTREXATE; CYCLOSPORINE; ADOLESCENTS; MODERATE